PENINGKATAN KREATIVITAS MELALUI METODE PROYEK DI PAUD AISYIYAH BUSTHANUL ATFHAL 3 PONTIANAK TENGGARA - Alayinda, Alma; Ali, Muhammad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was carried out as an effort to improve the creativity of early childhood. The research problem is